Investigating the Common Causes and Types of Epilepsy in Children: A Comprehensive Analysis of Risk Factors and Clinical Classifications - Habeeb Ullah, Muhammad Yousuf, Muhammad Sajid Akhtar, Ateeq Ur Rehman, Asif Javeed, Hafiz Farhan Shoukat (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Epilepsy is a prevalent neurological disorder in children, characterized by recurrent seizures. Understanding the underlying causes and the different types of epilepsy is essential for optimizing treatment strategies. This study focused on identifying the common causes and clinical classifications of epilepsy in children, providing a comprehensive overview of associated risk factors. Aim: The aim of this study was to investigate the common etiologies, risk factors, and types of epilepsy in pediatric patients to offer insights for better diagnosis and management. Methods: A retrospective analysis was conducted on 150 pediatric epilepsy cases admitted to a tertiary care hospital between January 2020 and December 2022. Medical records were reviewed for demographic data, family history, perinatal factors, and neurological assessments. Epilepsy types were classified based on clinical presentations and electroencephalographic findings, while potential risk factors were identified through statistical analysis. Results: The most common cause of epilepsy in children was genetic predisposition (42%), followed by prenatal brain injury (25%) and central nervous system infections (18%). Generalized epilepsy accounted for 55% of cases, while focal epilepsy constituted 35%. Other types included idiopathic and syndromic forms, each contributing to 5% of cases. Family history of epilepsy and prenatal complications were significant risk factors, with odds ratios of 3.2 and 2.8, respectively. Conclusion: The findings highlighted those genetic factors and prenatal complications were major contributors to childhood epilepsy. Generalized epilepsy was the predominant type observed. Early identification of risk factors may facilitate timely intervention and improve outcomes for pediatric patients with epilepsy. Keywords: Pediatric epilepsy, genetic predisposition, risk factors, generalized epilepsy, focal epilepsy, clinical classification